Going Local: An Examination of the LCBO and the Ontario Wine Industry - Nash, Nathaniel A. (My University, 2010)
Once thought of as a region that would never be able to produce quality wine from its own land, the Ontario wine industry has seen many evolutions, just as the global wine industry has. Ontario wines have since proven the naysayers of the Old World wrong as they have received overwhelming amounts of international awards and accolades for its traditional varietals, its unique hybrids, and its highly sought after Icewines. However, Ontario residents still seem to be reluctant to put their faith in the local industry as Ontario wines only represent 42% of Ontario wine sales, with the remaining 58% being controlled by a highly competitive import market. To put this into perspective, most wine regions control at least 80% of their own local market. Furthermore, this issue is exasperated due to the fact that the Ontario wine market is running on a monopoly retail and distribution system that is owned and operated by the Ontario government.
With many other wine regions around the world receiving plenty of support from their governments, how is it that a retail system which is operated entirely by a Crown Corporation cannot support its own wine industry and achieve a majority of sales in the local market? If Ontario wines are being praised on a global scale, what is preventing them from being fully adopted by local customers? If sales in a capitalist market are driven by marketing, advertising, and promotional measures, is this an issue of failed techniques or a complete lack thereof? If Ontario wines, by international standards, are worthy of attention, it seems that there is a communication error that is not expressing the value of Ontario wines to Ontario customers. But who is to blame? To answer these questions and uncover the promotional relationship between the Crown Corporation and the Ontario wine industry, I will perform a historical analysis to examine the political economic conditions surrounding the Ontario wine industry. To further qualify this historical analysis, I will conduct interviews with members of the Ontario wine industry with hopes of developing an understanding from the perspective of those directly involved in the industry.
Keywords: promotionalism; promotion; marketing; political economy; wine; local; tourism; LCBO; Advertising and Promotion Management; Agricultural and Resource Economics; Marketing; Other Communication; Political Economy; Public Policy; Public Relations and Advertising; Advertising and Promotion Management